Change Management Model in Start-Up at Incubator Business Technology UNAIR During a Pandemic - Prasetiyo, Bagus Dwi; Suryanto, Suryanto (Jurnal Ilmiah Sumber Daya Manusia, 2023)
The Covid-19 pandemic which has spread almost all over the world has paralyzed various sectors. This also has an impact on existing business developments, according to Mulya (2020) there was a significant decrease in the company's income during the Covid-19 pandemic. Same situation also hits most start-up of Business Incubator the Universitas Airlangga Surabaya . For this reason, new strategy is required to survive; so that start-ups in Universitas Airlangga Business Incubator is stable and keep being productive during the Covid-19 pandemic. The purpose of this study is to find out the strategies carried out by start-ups which are placed  at the Universitas Airlangga Business incubator  for survival during the crisis times and how they respond to Change Management. This study uses qualitative methods for descriptive purposes. The implementation of this method is conducted by using online observation. In this Covid-19 Pandemic, it requires them, to apply change management. The change management they create goes through four important phases, namely Rejection, Resistance, Exploration and Commit. The Exploration phase is the most important phase in realizing change management so that the company does not go downhill. Also by the observations, researcher find out that in this phase, start-up trigerred to  find new solution and innovation in maintaining business stability in the midst of the Covid-19 Pandemic. Because this research uses qualitative methods, the research results cannot be used as a guide in other companies. For this reason, further research is expected to use quantitative methods to determine the relationship of change management to other factors along with applicable approaches. The novelty in this research is to examine the most important phase in change management at start-ups of Universitas Airlangga Business Incubator when experiencing an uncertain situation (covid-19 pandemic).